Pain in female dancers and dance teachers: Perception, assessment, and related behavior - Lampe, J.; Groneberg, D. A.; Ohlendorf, D.; Wanke, E. M. (Scandinavian Journal of Medicine & Science in Sports, 2019)
Pain experiences are almost unavoidable in dance and involve a health hazard potential. In dance, certain self-endangering attitudes and behavior patterns toward pain are emerging. Especially for female dancers (Ds) and dance teachers (DTs) of the non-professional levels, pain is still insufficiently recorded. The aim of this study was to compare the subjective perception of pain, its assessment, and the pain behavior of female dancers and dance teachers of the non-professional dance level. Methods: The data were collected by a quantitative descriptive cross-sectional study using an online questionnaire in n = 205 Ds and n = 151 DTs. The dance-associated pain characteristics were analyzed in n = 171 Ds (83.4%) and n = 130 DTs (86.1%). Results: The sensory and affective perception of pain was more pronounced in DTs than in Ds. Unlike Ds, DTs rather evaluated pain as signal of a (potential) injury. The majority of the subjects continued their dancing activity to its full extent or under a gentle change of behavior patterns. As to pain treatment, preference was given to self- or medical and therapeutic treatment. Strategies of physical tension regulation were often used in pain management. Conclusions: Even in pain, the majority of female dancers and dance teachers of the non-professional level continued their dancing activity. However, there seemed to be a health-conscious coping with pain, especially in the DTs. Medical and therapeutic treatment was frequently used.